Study of the Extension of Plant Protection Measures in Agricultural Production - Planning Commission (Planning Commission, 1968)
"During the last fifteen years er so chemical measures to control pasts, diseases and words have progressively gained in popularity although they are far from the required scale of adoption, The plant protection measures can be broadly classified into four groups:"
Programme Evaluation Organisation Planning Commission Government of India